Emission and theoretical studies of Schiff-base [2+2] macrocycles derived from 2,2′-oxydianiline and zinc complexes thereof - Wang, Kuiyuan; Chen, Kai; Bian, Tiezheng; Chao, Yimin; Yamato, Takehiko; Xing, Feng; Prior, Timothy J.; Redshaw, Carl (Dyes and Pigments, 2021)
The emission properties of a number of solvates of the [2+2] Schiff-base macrocycles {[2-(OH)-5-(R)-C6H2-1,3-(CH)2][O(2-C6H4N)2]}2 (R = Me L1H2, tBu L2H2, Cl L3H2), formed by reacting 2,6-dicarboxy-4-R-phenol with 2,2′-oxydianiline (2-aminophenylether), (2-NH2C6H4)2O, have been investigated. Macrocycles L1-3H2 exhibited different maximum emission wavelengths in different solvents, from max at 508 nm (in acetonitrile) to 585 nm (in dichloromethane). DFT studies on systems L1-3H2 involving solvents of different polarity (DMF versus n-hexane) indicated that the energy level gap increases with solvent polarity in line with the observed hypochromic shifts. Reaction of macrocycle L1H2 with three equivalents of ZnBr2, in the presence of Et3N, affords the complex [(ZnBr)(ZnNCMe)L1]2[ZnBr4]·2.5MeCN (1·2.5MeCN). In the case of L2H2, reaction with two equivalents of ZnBr2 affords [(ZnBr)L2H2][ZnBr3NCMe]·3MeCN (2·3MeCN), whilst in the presence of two equivalents of Et3N, work-up led to the isolation of the complex [(ZnBr)2L2]·4.5MeCN (3·4.5MeCN). The molecular structures of 1, 2 and 3 are reported, together with their emission behaviour.
Keywords: Schiff-base; Macrocycle; Solvents; Emission; DFT studies